2022
DOI: 10.1002/env.2751
|View full text |Cite
|
Sign up to set email alerts
|

Association between air pollution and COVID‐19 disease severity via Bayesian multinomial logistic regression with partially missing outcomes

Abstract: Recent ecological analyses suggest air pollution exposure may increase susceptibility to and severity of coronavirus disease 2019 (COVID‐19). Individual‐level studies are needed to clarify the relationship between air pollution exposure and COVID‐19 outcomes. We conduct an individual‐level analysis of long‐term exposure to air pollution and weather on peak COVID‐19 severity. We develop a Bayesian multinomial logistic regression model with a multiple imputation approach to impute partially missing health outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Other studies have reported associations between short term exposures to fine particulate matter (PM 2.5 ) and COVID-19 infection, hospitalizations, and mortality ( Solimini et al, 2021 ; Xu et al, 2022 ; Zhu et al, 2020 ). Associations with long-term exposure to PM 2.5 and COVID-19 morbidity and mortality in the United States and Colorado specifically have also been documented ( Hoskovec et al, 2022 ; Berg et al, 2021 ; Bowe et al, 2021 ; Marquès and Domingo, 2022 ; Wu et al, 2020 ). However, limited studies have examined the concurrent effects of the pandemic and WFS on all-cause mortality or for causes other than COVID-19.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Other studies have reported associations between short term exposures to fine particulate matter (PM 2.5 ) and COVID-19 infection, hospitalizations, and mortality ( Solimini et al, 2021 ; Xu et al, 2022 ; Zhu et al, 2020 ). Associations with long-term exposure to PM 2.5 and COVID-19 morbidity and mortality in the United States and Colorado specifically have also been documented ( Hoskovec et al, 2022 ; Berg et al, 2021 ; Bowe et al, 2021 ; Marquès and Domingo, 2022 ; Wu et al, 2020 ). However, limited studies have examined the concurrent effects of the pandemic and WFS on all-cause mortality or for causes other than COVID-19.…”
Section: Discussionmentioning
confidence: 95%
“…Because of the potential for delayed effects of wildfire smoke or PM 2.5 and COVID-19 infection on mortality, we also considered the rolling period of the previous 11 days in our models. The 11-day period represents the average time between COVID-19 diagnosis and death among Denver residents ( Hoskovec et al, 2022 ). All models included indicator variables for year (where 2010 was the reference year) and day of week (where Sunday was the reference day).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Penelitian di Colorado, juga menunjukkan bahwa peningkatan paparan tahunan PM2,5 pada tahun sebelum pandemi dikaitkan dengan peningkatan risiko hasil COVID-19 yang parah. 56 Pada penelitian meta analisis menghasilkan bahwa infeksi dan kematian COVID-19 di Asia berkorelasi dengan PM2,5, tetapi dengan pengaruh variabel lainnya. 57 Saat PM2,5 beradhesi dengan virus SARS-CoV-2 maka PM2,5 membantu dalam penyebaran virus SASR-CoV-2.…”
Section: Hubungan Pm25 Dengan Kasus Konfirmasi Covid-19unclassified
“…Air pollution has become a serious threat to human health (Hoskovec et al, 2022), particularly in urban areas and cities (Antanasijević et al, 2018; Cromar et al, 2020; Dominici et al, 2000). The World Health Organization (WHO), the European Commission, and several International Organizations and Institutions have proposed policy strategies to reduce air pollution in cities, and its damage to health (EEA, 2022; WHO, 2021).…”
Section: Introductionmentioning
confidence: 99%